Single or double needle insertion in twin's amniocentesis: Does the technique influence the risk of complications? - E. Krispin; A. Wertheimer; S. Trigerman; A. Ben-Haroush; I. Meizner; A. Wiznitzer; R. Bardin (Elsevier, 2019)
Objective: To compare complication rates following amniocentesis in twin gestations, according to sampling technique and number of needle insertions.Study design: A retrospective cohort study of all women with twin gestations who underwent amniocentesis and delivered in a single university affiliated medical center during 2002−2016. Amniocentesis was performed either through one uterine entry with passage through the inter-twin membrane or through two different entries to the two amniotic sacs. Pregnancy outcome of women that underwent single needle insertion amniocentesis, was compared to this of double needle insertion. Primary outcome was neonatal complications within 4 weeks after amniocentesis (late abortion, chorioamnionitis, preterm premature rupture of membranes, or hospitalization due to related symptoms). Secondary outcomes were gestational week at delivery and labor characteristics.Results: The study group comprised 212 women. Of them, 73 (34.4%) underwent a single uterine insertion and 139 (65.6%) two separate needle insertions. Baseline characteristics did not differ between the groups. The amniocentesis complication rate was 13.7% in the single insertion group and 16.5% in the double insertion group (p = 0.587). Multivariate analysis found that a single insertion method had no statistically significant influence on complication rate, after making adjustments for potential confounders (OR = 1.085, 95% CI 0.4-2.9; p = 0.871). Other labor characteristics were similar between the groups.Conclusion: Needle insertion technique in twin gestation amniocentesis was not associated with procedure related complications. Keywords: Twin pregnancy, Amniocentesis, Abortion, Needle insertion